Dislocation interactions at reduced strain rates in atomistic simulations of nanocrystalline Al. (1st February 2018) - Dupraz, Maxime; Sun, Zhen; Brandl, C.; Van Swygenhoven, Helena
Abstract: Molecular dynamics simulations of transient stress drops have been carried out in different regimes on a nanocrystalline Aluminum sample with average grain size of 12 nm. Besides confirming the interpretation of experimental results obtained during in situ X-ray diffraction, the creep simulations performed at 2 or 3 orders of magnitude lower strain rates than usual reveal deformation mechanisms that have not been observed previously. First of all, it is evidenced that the misfit dislocations available at the GB assist the propagation of a lattice dislocation on a plane with low resolved shear stress. Furthermore, it is shown that the interaction of two dislocations gliding on parallel slip planes can result in the emission of a vacancy in the grain interior. Finally, the importance of the Schmid factor in the activation of slip in nanocrystalline structures is discussed. Graphical abstract: Image 1